2014
DOI: 10.6018/analesps.30.3.168901
|View full text |Cite
|
Sign up to set email alerts
|

Tipología circadiana y problemas de salud mental

Abstract: Resumen: La tipología circadiana (matutina, vespertina o intermedia) es una diferencia individual que se ha relacionado con numerosos aspectos de la salud mental. En este estudio se revisan los principales hallazgos publicados en el área. Tras la búsqueda bibliográfica en las principales bases de datos se seleccionaron un total de 70 artículos publicados en castellano e inglés entre los años 1990 y 2012, recogidos en las bases de datos ISI, Scopus y Medline, donde se muestra que los individuos vespertinos pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 122 publications
1
3
0
Order By: Relevance
“…Nevertheless, the non-interaction observed between sex and circadian typology indicates that circadian typology results are independent of sex. The higher tendency to hold negative beliefs of uncontrollability and danger, to distrust the own memory and to stay continuously aware of self-thinking observed in evening-type supports the assumption of this typology as a risk factor for the development of different psychological problems and pathologies [9,11], as these metacognitive beliefs are related to diverse problems such as drug consumption and addictive behaviors [47,77,78], anxiety and stress [45,46,79] and depressive symptomatology [41,80,81], among others.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Nevertheless, the non-interaction observed between sex and circadian typology indicates that circadian typology results are independent of sex. The higher tendency to hold negative beliefs of uncontrollability and danger, to distrust the own memory and to stay continuously aware of self-thinking observed in evening-type supports the assumption of this typology as a risk factor for the development of different psychological problems and pathologies [9,11], as these metacognitive beliefs are related to diverse problems such as drug consumption and addictive behaviors [47,77,78], anxiety and stress [45,46,79] and depressive symptomatology [41,80,81], among others.…”
Section: Discussionsupporting
confidence: 60%
“…During the last decades there has been an increase in the interest in studying the associations between morningness-eveningness and the so-called circadian typologies and mental health related-factors such as satisfaction with life and well-being [1,2], resilience and optimism [3], emotional intelligence [4], maladaptive coping strategies [5], personality traits related to risk behaviors [6], psychological symptoms [7,8] and psychopathology [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although in the present study we found an important interaction between the evening chronotype and sleep quality, Yıldırım and Boysan [ 36 ] using signal detection analysis could not find a significant association between circadian preferences and sleep quality in healthy individuals from Turkey. Similarly, Antúnez, Navarro and Adan in a systematic review [ 37 ] reported that there were no differences in time or quality of sleep between evening and morning individuals, although the latter tended to get up and go to bed two or three hours earlier according to polysomnographic records if they were free to choose schedules. However, if subjects with an evening chronotype had to get up early, it was less frequent that they felt asleep; sleep had a shorter duration and a nap was more usually required.…”
Section: Discussionmentioning
confidence: 99%